Literature studies on natural disasters and communication in Indonesia - Oktavia Yenny; Khairani Wardah Nabila (E3S Web of Conferences)
Disaster communication is important in improving community preparedness because it can help convey information and instructions for the community to face and respond to disasters effectively. This study aims to analyse the role of communication in disaster management in Indonesia based on a review of various related literature sources. The research uses literature study approach, analysing the publication of communication science journals discussing communication and natural disasters in Indonesia. The data sources include various relevant scientific publications, since the year 2000. The results showed that: 1) The types of natural disasters that are the main concern in the publication of communication journals in Indonesia are disasters on a national and regional scale such as floods, earthquakes, tsunamis, and volcanic eruptions. 2) Various communication topics include disaster communication for community mitigation and preparedness, public communication and social media in disasters, crisis communication and disaster communication management, communication and community participation in disasters, as well as disaster communication and vulnerability issues of vulnerable groups. 3) Efforts to bridge the gap between research and disaster management practice are challenges that must be faced so that communication science can make a greater contribution to improving the effectiveness of disaster management and mitigation in Indonesia.